The Economics of Silicon Applications on Rice and Sugarcane in Florida - José Alvarez; Lawrence E. Datnoff; George H. Snyder (EDIS)
The purpose of this document is to summarize previous economic information on silicon applications to rice and sugarcane in the EAA and to make this information available through EDIS. These summaries will be provided for monocultures of rice and sugarcane and for rice-sugarcane rotation production. Growers overwhelmingly use silicon applications for rice-sugarcane rotations in Florida. This is EDIS document FE475, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published May 2004.